Islamic Philantropy sebagai Alternatif Penyejahteraat Umat melalui Program Zakat Produktif - Afandi, Akhmad Jazuli; Nabila, Dian (Al-Muhasib: Journal of Islamic Accounting and Finance, 2021)
The spread of the Covid-19 pandemic in various countries, especially Indonesia, is the background of this research. This pandemic has hurt people's livelihoods in various fields. These impacts cover the economic, educational, health, social, and religious fields. In handling the impact of Covid-19, collaboration with the government and elements of society is needed, and Islamic philanthropic institutions in charge of zakat management occupy a strategic position. This study seeks to answer the question, how is the contribution of the institution to the welfare of the people who are economically affected by the pandemic. Then, the purpose of this study is to find out how the distribution mechanism of productive zakat is one of the superior products of community empowerment. LAZISNU MWC Kertosono was used as an object of observation and showed the results that, through the program launched, namely business capital financing, it had succeeded in becoming an alternative to improving the welfare of mustahik al-zakat